Construction of stimuli-responsive supramolecular gel via bispillar[5]arene-based multiple interactions. Issue 13 (15th March 2017) - Wei, Tai-Bao; Chen, Jin-Fa; Cheng, Xiao-Bin; Li, Hui; Han, Bing-Bing; Yao, Hong; Zhang, You-Ming; Lin, Qi
Abstract : A linear supramolecular polymer has been constructed from host–guest recognition. Furthermore, the linear supramolecular polymer could self-assemble to form a supramolecular gel at high concentration, which exhibited external stimuli-responsiveness. Abstract : A linear supramolecular polymer has been constructed from host–guest recognition of two complementary homoditopic monomers, a novel bispillar[5]arene and a bipyridinium salt derivative. Furthermore, the linear supramolecular polymer could self-assemble to form a supramolecular gel at high concentration, which exhibited external stimuli-responsiveness. When the competitive guest adiponitrile was added to the viscous solution at high temperature, the obtained solution could not form a supramolecular gel on cooling. Moreover, this gel could effectively sense Fe 3+ with specific selectivity. Simultaneously, a thin film based on the supramolecular gel was prepared, which was confirmed to be a convenient test kit for detecting iron ions.